Metacognition in nurse practitioner students: How nurse educators can best serve their students. Issue 12 (9th December 2021) - Waryold, Justin M.; Holliday, Kathryn; Rodriguez, Eric
Abstract: The dynamic and changing healthcare environment requires educators to prepare nurse practitioner students with more than knowledge and skills. Healthcare providers need to be prepared with enhanced skills related to critical thinking and decision making. Metacognition training has been used by many disciplines within and outside of healthcare to prepare individuals to work in an environment that has volatility, uncertainty, complexity, ambiguity, and delayed feedback (VUCAD). This retrospective exploratory study uses computerized strategic management simulation (SMS) data to address the question: What parameters of metacognition do master's level nurse practitioner (NP) students excel versus underperform? Elements of Presentation: Presentation will include SMS parameters linked with the National Organization of Nurse Practitioner Faculties (NONPF) Core Competencies. In doing this, faculty can better assess students' individualized learning needs and tailor their academic education to address specific needs. Fifty‐nine master's level students completed SMS, measuring five unique parameters of metacognition (Crisis, Task, Strategy, People & Information Management). Students' mean and median scores were observed to be high range for crisis management; and moderate range for task management, strategy management, and people management. Conversely, mean and median scores were in the low range for information management. Knowledge gained from this study can be used for curriculum development and planning to ensure that the parameters of metacognition are demonstrated throughout the curriculum's content delivery, training exercises, and evaluation methods. Knowledge related to areas in which NP students score in the low range can be added to courses to assist students better.